Chemopreventive Properties of Black Raspberries and Strawberries in Esophageal Cancer Review - Ni Shi; Tong Chen (Antioxidants, 2022)
Esophageal cancer is one of the most fetal malignancies in the world. Esophageal squamous cell carcinoma (SCC) and esophageal adenocarcinoma (AC) are two main types of esophageal cancer and each with distinct epidemiological, etiological and histopathological characteristics. The continued global prevalence of tobacco use and alcohol consumption, coupled with limited intake of fresh fruits and vegetables, ensures that esophageal cancer will remain one of the major health threats. In addition to promoting quitting smoking and alcohol abuse, one of the strategies of cancer prevention is to identify foods, food components, or dietary patterns that can prevent or delay the onset of esophageal cancer. A food-based approach has the advantage of a complex of mixtures of bioactive components simultaneously targeting multiple processes in carcinogenesis. We have employed a preclinical rodent model of esophageal SCC to assess the effects of black raspberries (BRB) and strawberries. Our investigations demonstrate that BRB and strawberries are potent inhibitors of esophageal cancer. To prepare for this review, a literature search was performed to screen BRB and strawberries against esophageal cancer using electronic databases from PubMed, Science Direct and Google Scholar. Search was conducted covering the period from January 2000 to June 2022. Our present review has provided a systematic review about chemopreventive effects of BRB and strawberries in esophageal cancer by collecting and compiling diverse research findings from the above sources. In this review, we discussed the anti-tumor potentials of BRB and strawberries in esophageal SCC and esophageal AC separately. For each cancer type, we discuss animal models and research findings from both animal bioassays and human clinical studies. We also discuss the potential mechanisms of action of berries and their key bioactive components.